INVESTIGATION INTO THE EFFECTS OF LOW SALINITY WATER ION COMPOSITIONS ON WETT ABILITY ALTERATION DURING FOAM FLOODING - SHABIB ASL, ABDOLMOHSEN SHABIB ASL (2016)
The ultimate goal of this work is to investigate the potential of a new hybrid EOR method termed Low Salinity Water Assisted Foam flooding (LSWAF). Typically. it consists of injecting Low Salinity Water (LSW) followed by an alternated injection of a Surfactant Aqueous Solution (SAS)and CO, gas. The selection ofLSW was based on its ability to produce signitlcant changes of rock wettability.